2019
DOI: 10.1002/jcb.28850
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of long‐noncoding RNAs and mRNA expression profiles in human steroid‐induced avascular necrosis of the femoral head

Abstract: This study performed the first microarray analysis of long‐noncoding RNA (lncRNA) and mRNA expression profiles in human steroid‐induced avascular necrosis of the femoral head (SAVNFH). Expression levels of lncRNAs and mRNAs in three human SAVNFH samples and three human femoral head fracture samples (controls) were detected using third‐generation lncRNA microarrays (KangChen Biotech, Shanghai, China). The fold change, false discovery rate, and P value were utilized to filter genes with significant differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…Complement and coagulation cascades was identified to be upregulated in ONFH cartilage, which reveals that they are involved in ONFH cartilage degeneration. This change was also observed in transcription analysis of bone tissue and serum proteome in patients with ONFH, respective 42,43 . Further investigation is expected about how these pathways are involved in the development of ONFH.…”
Section: Osteoarthritis Andcartilagesupporting
confidence: 59%
“…Complement and coagulation cascades was identified to be upregulated in ONFH cartilage, which reveals that they are involved in ONFH cartilage degeneration. This change was also observed in transcription analysis of bone tissue and serum proteome in patients with ONFH, respective 42,43 . Further investigation is expected about how these pathways are involved in the development of ONFH.…”
Section: Osteoarthritis Andcartilagesupporting
confidence: 59%
“…Osteocyte apoptosis is one of the most recognized causes of this disease at present. Studies have shown that the use of glucocorticoids can increase the death of osteoblasts and osteocytes and destroy the mechanical sensation of the bone cell network [26] . Bone trabeculae are sparse, bone mass is reduced, and osteonecrosis occurs.…”
Section: Theory Of Osteocyte Apoptosismentioning
confidence: 99%
“…Recent research results indicate that lncRNA also plays an important regulatory role in the pathogenesis and repair of ONFH. LncRNA was found to be differentially expressed in ONFH tissues, bone marrow mesenchymal stem cells and bone microvascular endothelial cells which isolated from ONFH patients ( 9 , 107 , 108 ). Functional research has further clarified its important role in the survival of osteoblasts closely related to ONFH and the osteogenic differentiation of bone marrow mesenchymal stem cells.…”
Section: Introductionmentioning
confidence: 99%